Nephroprotective Effects of Zataria multiflora Boiss. Hydroalcoholic Extract, Carvacrol, and Thymol on Kidney Toxicity Induced by Cisplatin in Rats. (27th January 2021) - Panahi kokhdan, Esmaeel; Sadeghi, Hossein; Kazemi, Shima; Doustimotlagh, Amir Hossein
Abstract : Background . Cisplatin (Cis) is an anticancer drug; however, it has dose-dependent renal toxicity. The current study aims to investigate the protective effects of Zataria multiflora Boiss. hydroalcoholic extract (Z.M.B), carvacrol, and thymol on cisplatin-induced nephrotoxicity in rats. Materials and Methods . Forty-two Wistar male rats were randomly allocated into six groups ( n  = 7). Group I received normal saline; group II received Cis (7 mg/kg. ip); group III received the Z.M.B extract only (500 mg/kg/d, po); group IV received Z.M.B extract (500 mg/kg/d, po) + Cis; group V received carvacrol (50 mg/kg/d, po) + Cis; and group VI received thymol (50 mg/kg/d, po) + Cis. The levels of biochemical markers, oxidative stress parameters, and histopathological staining were determined in serum and renal tissues. Also, the chemical compositions (carvacrol and thymol) of the Z.M.B extract were assayed by HPLC analysis. Result . The results revealed that Z.M.B extract, carvacrol, and thymol markedly decreased the renal index as compared with the Cis-only group. Also, carvacrol and thymol significantly reduced the blood urea nitrogen level as compared with the Cis-only group. Furthermore, Z.M.B extract, carvacrol, and thymol significantly attenuated the Cis-induced increase in malondialdehyde and nitric oxide metabolite. Additionally, histopathological examination showed that Z.M.B extract, carvacrol, and thymol markedly ameliorated Cis-induced renal tubular necrosis. Conclusion . The results showed renoprotective effects of Z.M.B extract, carvacrol, and thymol in Cis-induced nephrotoxicity in rats. Therefore, Z.M.B extract can be considered as a potential candidate for the protection of nephrotoxicity induced by Cis.